Knowledge of Antimicrobial Resistance and Associated Factors Among Health Professionals at the University of Gondar Specialized Hospital: Institution-Based Cross-Sectional Study - Simegn, Wudneh; Dagnew, Baye; Weldegerima, Berhanemeskel; Dagne, Henok (Frontiers in Public Health, 2022)
Background: Antimicrobial resistance is one of the health challenges worldwide, particularly in resource limited countries like Ethiopia. Increasing knowledge of health professionals can reduce the occurrence of antimicrobial resistance. In this study, we determined the antimicrobial resistance knowledge and examined the associated factors among University of Gondar Hospital health professionals. Methods: Institutional-based cross-sectional survey was carried out. The samples were recruited randomly. Statistical analysis was performed by using the statistical package for social sciences (SPSS) version 20 after entering the data using Epidemiological information (Epi-Info). To identify associated factors, the authors executed binary logistic regression where in the statistical significance was decided at p<0.05. Results: Four hundreds and twelve participants took part in the study with the mean age of 29.9 years, ranging from 20-60 years and 53.4% of participants were males. Of the total respondents, the majority of health professionals (84.7% [95% CI: (80.08-88.30)]) had good knowledge of antimicrobial resistance. Being male [AOR=1.94, 95% CI: (1.10, 3.52)], work experience 6-10 years [AOR=2.45, 95% CI: (1.28, 4.68)], working hours per week 30-38 hours [AOR=3.93, 95% CI: (1.38, 5.11)] and ever taking antibiotics [AOR=3.71, 95% CI: (1.75, 7.87)], were significant factors of antimicrobial resistance knowledge. Conclusion: The current study showed that good knowledge was 84.5% among study participants even though there might be a possibility of some difference among the health care professionals. We recommend the health administrators to update health care professionals by training to reduce the possibility of antimicrobial resistance emergence.